HEalth-Related Quality of Life-Intervention in Survivors of Breast and Other Cancers Experiencing Cancer-Related Fatigue and Associated Cognitive Symptoms Using TraditionAL Chinese Medicine: The ‘HERBAL’ Trial - Alexandre Chan PharmD; Daniella Chan BS; Ding Quan Ng BSPharm; Huang Fang Zheng MD; Quan Ming Tan MCM; Chia Jie Tan PhD; Jolene Hui Min Toh BS; Ning Yi Yap PhD; Yi Long Toh PhD; Yu Ke PhD; Edmund Chun Ann Wang BS; Queenie Pei Ni Lim BSocSc; et al. (Integrative Cancer Therapies)
Introduction: As pharmacological strategies remain limited for relieving fatigue and associated cognitive symptoms, integrative modalities such as traditional Chinese medicine (TCM) could be explored as therapeutic strategies in cancer survivors. Here, we evaluate and report the efficacy and safety of a TCM concoction, modified Xiang Bei Yang Rong Tang (XBYRT), on quality of life (QOL), cancer-related fatigue (CRF), and cognitive symptoms, compared to placebo. Methods: In a single-centered, randomized, double-blinded, placebo-controlled pilot trial conducted from 2019 to 2022, fatigued cancer survivors ≥21 years old were recruited to receive the XBYRT intervention or placebo (5% diluted) once daily for the duration of 8 weeks. Patient-reported outcomes for QOL, CRF, cognition, blood samples for biomarker testing, and adverse events were collected at baseline (T0), 4 weeks (T1), 8 weeks (T2), and 10 weeks (T3) after baseline. Linear regression was performed to evaluate differences between groups at T2 and T3. Results: A total of 1502 patients were screened, with 672 patients considered eligible. Of the eligible, 15 XBYRT and 13 placebo subjects with similar mean ages (58.5 vs 58.4) were recruited. Both groups were predominantly Chinese (93% vs 62%), breast cancer patients (87% vs 62%), and diagnosed with stage 2 cancer (60% vs 46%). Although no significant difference was found in QOL between groups, the XBYRT group exhibited improved emotional fatigue at T3 ( P  = .045) and higher BDNF levels at T2 ( P  = .047) and T3 ( P  = .029). After baseline adjustment, XBYRT was associated with better perceived cognitive impairment at T2 ( P  = .011) and T3 ( P  = .017), as well as overall perceived cognitive function at T3 ( P  = .028). XBYRT is well tolerated, with grade 3 adverse events reported in three XBYRT (20%) and two placebo (15%) subjects. Conclusion: In this pilot study, XBYRT as an integrative therapy is safe and generates encouraging improvements in cognitive and fatigue symptoms. Difficulties with recruitment limited the generalizability of trial findings, thus findings should be verified through a larger, multi-centered trial.